DITERMINAN MUTU PROSES SMK BISNIS-MANAJEMEN (Journal of Economic Education, 2012)
Tujuan penelitian : untuk mengetahui Determinan mutu proses SMK negeri bisnis manajemen di eks karesidenan Surakarta. Penelitian  ini menggunakan pendekatan  korelasional  dan survey. Populasi penelitian semua guru SMK bisnis-manajemen di Eks Karesidenan Surakarta sebanyak 666 orang, sampel diambil 200 orang dengan dengan teknik proporsional random sampling. Analisa data dengan permodelan persamaan structural (SEM).  Mutu proses SMK di Eks Karesidenan Surakarta dipengaruhi oleh : kompetensi guru, budaya organisasi, pembiayaan pendikan, kepemimpinan kepada sekolah dan peran komite sekolah. Pengaruh variabel bebas terhadap mutu proses  sebesar 64 % sisanya 36 % dipengaruhi faktor lain diluar model.  Temuan dapat diaplikasikan dalam rangka mempredeksi    Mutu proses di SMKN di Eks Karesidenan Surakarta dengan mengelola variabel eksogen. Prioritas pada kompetensi guru dan pembiayaan pendidikan   Abstract ___________________________________________________________________ The study aims to investigate determinants of quality process at State Vocational Schools (SMKN's) of Business Management in Ex-Residency of Surakarta. The study used a correlational and survey approach. The study population was all business-management vocational school teachers in the Ex-Residency of Surakarta with 200 people proportionally sampled out of the population (666 people). Data analysis was performed by employing Structural Equation Modeling (SEM). It turned out that the quality process at the vocational schools in Ex-Residency of Surakarta was influenced by teachers' competence, school organizational culture, education financing, school principals' leadership and school committee's role. Independent variables influence the quality of the process by 64%, the rest 36% influenced by other factors outside the model. The findings can be applied to predict the quality process at State Vocational Schools (SMKN's) of Business Management in Ex-Residency of Surakarta with managing the exogenous variables. Priority on the competence of teachers and education financing